Problematic Social Media Use and Intensive Social Media Use Among Academic Students During the COVID-19 Pandemic: Associations With Social Support and Life Satisfaction - Boniel-Nissim, Meyran; Alt, Dorit (Frontiers in Education, 2022)
The need for interaction that arose given the social distancing imposed on people by governments during the COVID-19 has increased the use of social media (SM). The current study distinguishes between two different patterns of SM use: problematic and intensive, and examines the impact of each specific type of SM on social and mental aspects (i.e., social support, loneliness, and life satisfaction). The sample included 363 higher education students. Data were gathered during a second lockdown using Partial Least Squares - Structural Equation Modeling. The model indicated two different trajectories corresponding to the two types of SM users: Intensive users reported having more family support, whereas problematic users tended to feel lonely, reported having low life satisfaction, and had less support from friends. This study may allude to the possible positive role of SM use, especially during social distancing, in alleviating social and mental burdens in times of crisis.